The structural basis of gas-responsive transcription by the human nuclear hormone receptor REV-ERBbeta. - Keith I Pardee (Public Library of Science (PLoS), 2009)
Heme is a ligand for the human nuclear receptors (NR) REV-ERBalpha and REV-ERBbeta, which are transcriptional repressors that play important roles in circadian rhythm, lipid and glucose metabolism, and diseases such as diabetes, atherosclerosis, inflammation, and cancer. Here we show that transcription repression mediated by heme-bound REV-ERBs is reversed by the addition of nitric oxide (NO), and that the heme and NO effects are mediated by the C-terminal ligand-binding domain (LBD). A 1.9 A crystal structure of the REV-ERBbeta LBD, in complex with the oxidized Fe(III) form of heme, shows that heme binds in a prototypical NR ligand-binding pocket, where the heme iron is coordinately bound by histidine 568 and cysteine 384. Under reducing conditions, spectroscopic studies of the heme-REV-ERBbeta complex reveal that the Fe(II) form of the LBD transitions between penta-coordinated and hexa-coordinated structural states, neither of which possess the Cys384 bond observed in the oxidized state. In addition, the Fe(II) LBD is also able to bind either NO or CO, revealing a total of at least six structural states of the protein. The binding of known co-repressors is shown to be highly dependent upon these various liganded states. REV-ERBs are thus highly dynamic receptors that are responsive not only to heme, but also to redox and gas. Taken together, these findings suggest new mechanisms for the systemic coordination of molecular clocks and metabolism. They also raise the possibility for gas-based therapies for the many disorders associated with REV-ERB biological functions.